Early lipid changes with atazanavir/ritonavir or darunavir/ritonavir. Issue 6 (12th January 2014) - Martinez, E; Gonzalez‐Cordon, A; Ferrer, E; Domingo, P; Negredo, E; Gutierrez, F; Portilla, J; Curran, A; Podzamczer, D; Murillas, J; Bernardino, JI; Santos, I; et al.
<x xml:space="preserve">Abstract</x> Objectives Ritonavir‐boosted atazanavir and darunavir are protease inhibitors that are recommended for initial treatment of HIV infection because each has shown better lipid effects and overall tolerability than ritonavir‐boosted lopinavir. The extent to which lipid effects and overall tolerability differ between treatments with atazanavir and darunavir and whether atazanavir‐induced hyperbilirubinaemia may result in more favourable metabolic effects are issues that remain to be resolved. Methods A 96‐week randomized clinical trial was carried out. The primary endpoint was change in total cholesterol at 24 weeks. Secondary endpoints were changes in lipids other than total cholesterol, insulin sensitivity, total bilirubin, estimated glomerular filtration rate, and CD4 and CD8 cell counts, and the proportion of patients with plasma HIV RNA < 50 HIV‐1 RNA copies/mL and study drug discontinuation because of adverse effects at 24 weeks. Analyses were intent‐to‐treat. Results One hundred and seventy‐eight patients received once‐daily treatment with either atazanavir/ritonavir (n = 90) or darunavir/ritonavir (n = 88) plus tenofovir/emtricitabine. At 24 weeks, mean total cholesterol had increased by 7.26 and 11.47 mg/dL in the atazanavir/ritonavir and darunavir/ritonavir arms, respectively [estimated difference −4.21 mg/dL; 95% confidence interval (CI) −12.11 to +3.69 mg/dL; P = 0.75]. However, the ratio of total to high‐density lipoprotein (HDL) cholesterol tended to show a greater decrease with atazanavir/ritonavir compared with darunavir/ritonavir (estimated difference −1.02; 95% CI −2.35 to +0.13; P = 0.07). Total bilirubin significantly increased with atazanavir/ritonavir (estimated difference +1.87 mg/dL; 95% CI +1.58 to +2.16 mg/dL; P < 0.01), but bilirubin changes were not associated with lipid changes. Secondary endpoints other than total bilirubin were not significantly different between arms. Conclusions Atazanavir/ritonavir and darunavir/ritonavir plus tenofovir/emtricitabine did not show significant differences in total cholesterol change or overall tolerability at 24 weeks. However, there was a trend towards a lower total to HDL cholesterol ratio with atazanavir/ritonavir and this effect was unrelated to bilirubin.